Proteomic profiling of a Sporobolomyces yeast reveals global responses to UV-B–induced oxidative stress - Ranko Gacesa; Raymond Chung; Suikinai Nobre Santos; Gabriel Padilla; Itamar Soares Melo; Paul F. Long (PLoS ONE, 2026)
Research background Ultraviolet-B (UV-B) radiation induces oxidative stress through the generation of reactive oxygen species, affecting organisms across all domains of life. While UV-stress responses have been extensively studied in the ascomycete yeast Saccharomyces cerevisiae and animal systems, little is known about the molecular mechanisms underlying UV tolerance in basidiomycete, UV-resistant yeasts. Carotenoid-producing yeasts of the genus Sporobolomyces represent an attractive model to investigate whether conserved oxidative stress pathways, including bZip transcription factor signalling analogous to the vertebrate Nrf2 pathway, contribute to UV tolerance. Experimental approach The UV-tolerant yeast Sporobolomyces sp. LEV-2 was exposed to UV-B irradiation for up to 24 hours. Quantitative multidimensional protein identification technology (MudPIT) mass spectrometry using tandem mass tag (TMT) labelling was applied to identify and quantify protein expression changes over time. Identified proteins were functionally annotated using InterProScan, KEGG tools and literature-based curation, and proteomic data were integrated with measurements of antioxidant activity and cell viability. Results and conclusions A total of 751 proteins were identified, including 105 stress-response proteins. UV-B exposure induced a coordinated oxidative stress response involving conserved signalling pathways (bZip, MAPK, FoxO, Ras and calcium signalling), antioxidant enzymes, heat-shock proteins and DNA repair factors. A bZip protein (LEV-2_XP_007274754.1) displayed Nrf2/Yap1-like behaviour, suggesting a central regulatory role in UV-induced stress signalling. A four-step model of UV adaptation was proposed, encompassing signalling, metabolic stress, antioxidant-driven adaptation and establishment of a stress-resistant state. These responses closely parallel UV- and oxidant-induced stress responses described in other fungi and in animal cells. Novelty and scientific contribution This study provides the first proteome-level analysis of UV-B stress adaptation in a Sporobolomyces yeast and demonstrate that UV tolerance relies on ancient, evolutionarily conserved oxidative stress mechanisms shared across eukaryotes, rather than yeast-specific pathways.